Malaysian Market Reaction to Announcement of Special Dividend Payment - Hashemi, Seyed Hamid (2011)
This research investigated the reaction of Malaysian stock market participants towards the announcement of payment of special dividends. Results show that there is a significant positive reaction from market participants toward the announcement of payment of special dividends on the first,second and fourth days after the announcement day.